Methanol conversion to dimethyl ether over beta zeolites derived from bagasse fly ash - Assawasangrat, Pornsawan; Neramittagapong, Sutasinee; Pranee, Watcharakorn; Praserthdam, Piyasan (My University, 2016)
Catalytic performance of beta zeolites derived from bagasse fly ash for methanol dehydration to dimethyl ether, alternative fuel, was investigated. Amorphous silica extracted from bagasse fly ash, a tetraethylammonium hydroxide (TEAOH) were used as a precursor and a template for synthesis of beta-zeolites, respectively. Beta zeolites could be synthesized at a constant hydrothermal temperature of 135°C and a constant initial pressure of 3 bars under the nitrogen atmosphere. The crystallization time and Si/Al ratio were 48 h and 15, respectively. These conditions gave the highest crystallinity for beta zeolites with a crystal size of 0.51 μm as well as a Brunauer–Emmett–Teller surface area of 844 m2 g−1. Beta zeolites with the Si/Al ratios of 15.8 and 24.6 were used as catalysts for methanol conversion to dimethyl ether. Beta zeolites with the Si/Al ratios of 15.8 and 24.6 have the % yields of 84 and 60, respectively. According to the result of NH3-TPD, the beta zeolites with the Si/Al ratio of 15.8 showed higher acidity than beta zeolites with a Si/Al ratio of 24.6. Therefore, the beta zeolites with a Si/Al ratio of 15.8 were more efficiency in methanol conversion reaction than beta zeolites with a Si/Al ratio of 24.6.
Keywords: Alternative energy; bagasse; beta zeolites; dimethyl ether; fly ash; methanol conversion